Assisted tree migration in North America: policy legacies, enhanced forest policy integration and climate change adaptation. Issue 6 (18th August 2017) - Wellstead, Adam; Howlett, Michael
ABSTRACT: The weight of much expert forest management opinion is that issues such as climate change can be effectively addressed only if forest policy-making moves from a purely sectoral focus and undergoes a shift to a more integrated multi-issue, multi-sector policy-making process. This is because credible adaptation policies in the sector require greatly enhanced multi-sectoral policy integration if they are to succeed. But this requirement may be beyond the capacity of many countries to deliver. This article explores the integration challenges faced by forest policy-making in Canada and the United States and uses the case of assisted tree migration to probe the reasons for the failure of institutions in both countries to develop and manage better vertical and horizontal integration in a climate change-related forest policy area. The article emphasizes the importance of previous rounds of policy-making or "policy legacies", which serve to constrain contemporary policy options. It argues that due to the presence of many such legacies, forest policy development will continue to feature incremental adjustments through policy layering and policy drift, processes which limit the prospects for greater integration and better climate change adaptation in this sector.